2018
DOI: 10.2147/copd.s184212
|View full text |Cite
|
Sign up to set email alerts
|

New evaluation of trunk movement and balance during walking in COPD patients by a triaxial accelerometer

Abstract: BackgroundIndividuals with COPD may experience ambulatory difficulty due to both effort intolerance arising from respiratory dysfunction and impaired balance control during walking. However, the trunk movement during walking has not been evaluated or adjusted for patients with COPD. The Lissajous index (LI) visually and numerically evaluates the left–right symmetry of the trunk movement during walking and is useful in clinical practice. In COPD patients, the LI is used as an indicator of the left–right symmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…In the included studies, “static stability” was assessed for several conditions of visual status (eyes open / eyes closed), stance (natural stance, tandem stance, one leg stance) or surface (stable / unstable surface, foam). A significant alteration of the component was found in the majority of studies: on thirty-five studies comparing COPD and healthy subjects, thirty studies reported a significant decrease in COPD group (twenty-six studies assessing “static stability” in isolation [2651], four studies with composite tests [52–55]), four studies found no significant differences between groups [5659] and data were not available in one study [60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the included studies, “static stability” was assessed for several conditions of visual status (eyes open / eyes closed), stance (natural stance, tandem stance, one leg stance) or surface (stable / unstable surface, foam). A significant alteration of the component was found in the majority of studies: on thirty-five studies comparing COPD and healthy subjects, thirty studies reported a significant decrease in COPD group (twenty-six studies assessing “static stability” in isolation [2651], four studies with composite tests [52–55]), four studies found no significant differences between groups [5659] and data were not available in one study [60].…”
Section: Resultsmentioning
confidence: 99%
“…Some studies using laboratory gait analysis identified impairments in parameters related to “dynamic stability” in COPD patients: alteration of margins of stability (in medio-lateral direction) and its variability [75] and increase of centre of mass medio-lateral sway [60] and acceleration variability [76].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant alteration of the component was found in the majority of studies: on thirty-five studies comparing COPD and healthy subjects, thirty studies reported a significant decrease in COPD group (twenty-six studies assessing "static stability" in isolation , four studies with composite tests [52][53][54][55]), four studies found no significant differences between groups [56][57][58][59] and data were not available in one study [60].…”
Section: [Insert Fig4]mentioning
confidence: 99%
“…These three studies were consistent to identify dynamic stability sub-component as one of the most impaired among all postural control sub-component. Some studies using laboratory gait analysis identified impairments in parameters related to "dynamic stability" in COPD patients: alteration of margins of stability (in medio-lateral direction) and its variability [75] and increase of centre of mass medio-lateral sway [60] and acceleration variability [76].…”
Section: Dynamic Stabilitymentioning
confidence: 99%